Exit strategies - Ignazio Angeloni; Ester Faia; Roland C. Winkler (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We study alternative scenarios for exiting the post-crisis fiscal and monetary accommodation using the model of Angeloni and Faia (2010), that combines a standard DSGE framework with a fragile banking sector, suitably modified and calibrated for the euro area. Credibly announced and fast fiscal consolidations dominate - based on simple criteria - alternative strategies incorporating various degrees of gradualism and surprise. The fiscal adjustment should be based on spending cuts or else be relatively skewed towards consumption taxes. The phasing out of monetary accommodation should be simultaneous or slightly delayed. We also find that, contrary to widespread belief, Basel III may well have an expansionary macroeconomic effect.
urn:nbn:de:hebis:30-87138
Keywords: G01; E63; H12; 330; Exit Strategies; Debt Consolidation; Fiscal Policy; Monetary Policy; Capital Requirements; Bank Runs